Quality Analysis and Anti-termite Activity of Essential Oils from the Leaves, Stems, and Roots of Litsea firma (Blume) Hook F - Gerina, Febrilia; Muharini, Rini; Lestari, Ira; Masriani, Masriani; Enawaty, Eny (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Litsea firma (Blume) Hook. f. has long been utilized as a traditional medicine plant. This research aims to analyze the quality of L. firma (Blume) Hook F essential oils extracted from its leaves, stems, and roots and to evaluate their anti-termite activity. The essential oils were obtained using the steam-water distillation method for 8 hours in triplicate. The quality of the essential oils was determined by their yield, specific gravity, refractive index, and optical rotation angle, which was compared with the previously reported quality data of L. cubeba essential oil. The results showed that all L. firma essential oils possessed a transparent colour, a distinctive aroma, and a bitter taste. The quality assessment revealed that essential oil yields ranged from 0.16% - 2.42%. The specific gravity of leaves essential oil was 0.83. Furthermore, the refractive index ratio ranged from 1.43 to 1.44, and the optical rotation angle varied between +15.3° to +16.8°. Phytochemical analysis revealed the presence of terpenes in L. firma essential oil. Essential oil of L. firma leaves exhibited a pronounced anti-termite activity with a percentage mortality of 100% and paper weight loss of 11.6 %. Thus, L. firma essential oils, particularly from leaves, had promising potential for natural termite control.